Iazyk moy pouczytsia prawdi twoiey»: слов’яноруські вставки польською графікою у трактаті Лазаря Барановича - Геращенко, Ольга М.; Штефан, Антон П. (Slavia Occidentalis, 2022)
The article draws attention to the Slavenrosska phonetics analysing the Slavenorosski insertions in Polish graphics in Lazar Baranovych’s theological treatise “Notiy pięć ran Chrystvsowych pięс” (1680). These insertions reflect the epoch’s tendencies in pronouncing the Slavenorosski texts by the speakers of Northern Ukrainian (Eastern Polisyen) patois, e.g. prove the well-established pronunciation of ѣ as [і]. The pronunciation of labials, velars, pharyngeal and [н’] before the front vowel [і] was systematically soft. The sibilant sounds, on the contrary, were hard (the corresponding letters were always followed by a y, not an i). The variations ri/ry, ti/ty, li/ly, si/sy, di/dy show an [и] sound that replaced the former [i], and the history of language corroborates this fact. The document presents the palatalized pronunciation of velars as well as the pharyngeal before the front vowel (it surely was an [i]) replacing their hard pronunciation before vowels). The hard pronunciation of consonants before an [e] and the fricative pronunciation of Slavenorosska г was confirmed. The Cyrillic щ was pronounced as a combination of two hard sibilants [шч]. The treatise recorded the hard pronunciation of the final stem sound [р] while the etymologically soft pronunciation inside the stem remains systematically intact. The document records the hard pronunciation of [ц] at the stem end of masculine nouns. The nominative and accusative forms of singular masculine adjectives are mostly pronounced with a reduced final [ǐ]. Proper names of Greek origin could have a fricative or, less frequently, a plosive pronunciation in lieu of γ, ѳ mainly sounded as [фт]. In the king’s name, it was transliterated as th.